Ekstrak Daun Keji Beling (Strobilanthes crispus L.) Uuntuk Penurunan Kadar Kolesterol Pada Tikus Putih Jantan (Ratus norvegicus) Galur Wistar: Keji Beling (Strobilanthes crispus L.) Leaf Extract for Reducing Cholesterol Levels in Male White Rats (Ratus norvegicus) Wistar strain - Rachman, Fadila Abd; Ardiansyah, Syahrul (Medicra (Journal of Medical Laboratory Science/Technology), 2019)
Indonesian citizens have a various lifestyle impacts on the increasing of blood-cholesterol level. One of the potential herbal medicine is keji beling leaves (Strobilanthes crispus L.) because of these leaves contains flavonoid and sterol. This study aims to analyze the efficacy of Strobilanthes crispus L. leaves extract to decrease the blood-cholesterol level. This research is experimental laboratory with pretest – post test only control group design. The total of 24 Wistar rats were divided into six groups, as follow: negative control, positive control, treated with 25%, 50%, 75% and 100% Strobilanthes crispus L. extract. The therapy was administrated for 14 days. Cholesterol test using POCT method. The data were analyzed using Repeated Measured Anova. The results showed that Strobilanthes crispus L. leaves extracts potentially decreased on blood-cholesterol level in Wistar rats after 14 days of treatment. This study reflected that the Strobilanthes crispus L. leaves extract can be used as the alternative therapy on the blood-cholesterol level. The greatest decrease in P4 (100% concentration).